The Association between Early Marriage Decisions and Poverty Incidents in Indonesia - Najwa Khairina; Muhammad Azhar Tridharma Putra (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
Early marriage is one of the social problems prevalent in many emerging countries, including Indonesia. Early marriage is widely believed to impact future economic outcomes negatively and is also associated with higher poverty incidence. Previous research has shown that early marriage significantly affects an individual’s future welfare and makes them vulnerable to poverty (Dahl, 2010). Research on this issue is still limited in Indonesia, and we aim to pursue the impact of early marriage decisions on poverty, using divorce, dropout, and gender as control variables. We use panel logistic regression on Indonesia Family Life Survey (IFLS) data set. We classify early married individuals as someone who marry under 18 years old, while the poverty variable is measured using the national poverty line. The logistic regression shows that early marriage is significantly associated with lower wages and poverty. The marginal effect of the logistic regression shows that an individual who marries early has a higher probability of getting into poverty, as much as 13-15%. We also found that women are more vulnerable to poverty than male with the exact status of marriage and education level. This result implies that the early marriage problem needs further attention from the policymaker. Regulation of the age of marriage should be reinforced and supported by more stringent measures from local governments.